A study of epoxy nanocomposites insulating materials and its effects on electrical tree propagation - Izzwan Saad, Mohd. Hafiez (2013)
Polymeric insulating materials have attracted wide interest especially in high voltage equipments due to its potential properties enhancement. One of the main phenomena of partial discharges occurred in polymeric insulating material is electrical treeing phenomena. This kind of phenomena will cause excessive electric field stress at points where void and defects located. This thesis presents the thorough analysis of electrical treeing phenomena in epoxy nanocomposites. Epoxy resin nanocomposites containing 1 wt% and 3 wt%, of nanofillers sized organically modified montmorillonite (OMMT) nanoclay and silicon dioxide (silica) nanofillers were prepared and investigated, with unfilled epoxy resin served as reference material. The nanocomposites were prepared by using leaf-like specimen’s method and online monitoring method was used to test the samples. Electrical insulating properties, mainly the electrical tree resistance were investigated based on to IEC 1072:1991, “Methods of Test for Evaluating the Resistance of Insulation Materials against the Initiation of Electrical Trees”. There are three main parameters were collected during experiment was conducted which are tree inception voltage (TIV), tree breakdown voltage (TBV) and tree propagation time (TPT). Field emission scanning electron microscope (FESEM) was performed to determine the dispersion state of nanoclay epoxy resin nanocomposites. Based on the results, it was found that the existence of OMMT and silica nanofillers in polymer matrix could exhibit electrical tree growth. Furthermore, the presence of OMMT nanoclay in epoxy resin make tree growth faster compared the presence of silica nanofillers in epoxy resin.